THE RELEVANCE OF IBN SINA’S ISLAMIC ECONOMICS THOUGHTS TO THE PANCASILA ECONOMICS PARADIGM - Havis Arafik; Nur Rohim Yunus; Dwi Sulastyawati (Jurnal Ekonomi dan Kebijakan Publik Indonesia, 2019)
AbstractThis study aims to explain and study the other sideof IbnSina as the expert in Islamic economics.This is important because so far IbnSina hasalways been identified as a doctor, chemist, andphilosopher of Islam, and such identification isvery far from economic ideas. While manyeconomic ideas were originated from IbnSina. Hisworks such as as-Syifa and Risalah as-Siyasahhave sufficiently discussed about the economy.This study used a literature approach to describeand analyze the object of the research, namelyreading and reviewing various sources of thetopic, analyzing and finally drawing a conclusionwhich was further presented in the form of awritten report. The results of this study indicatedthat IbnSina was not only a well-known andworldwide physician, chemist, and philosopher,but also an Islamic economics thinker. Many ideasabout the economy were born from his works, as-Syifa and Risalah as-Siyasah, such the discussionsare about humans as economic agents; economicrevolutions as the main foundation of economicdevelopment; and welfare as well as prosperity asthe main goals of economic practice and stateadministration